The FinTech Dividend: How Much Money Is FinTech Likely to Mobilize for Sustainable Development? - Латковська, Тамара Анатоліївна; Латковська, Т. А.; Латковская, Тамара Анатольевна; Latkovska, Tamara A.; Michael, Bryane (Durham University, 2021)
FinTech offers a new way to mobilize resources for all kinds of uses – including for funding sustainable development. Roughly 3%–13% of funding required for the UN’s Sustainable Development Goals (SDGs)– or around $50 billion to $125 billion -- could come from a ‘FinTech Dividend.’ Such a dividend derives from the use of FinTech platforms to increase savings and investment (overall), channel resources into publicly-funded as well as privately-funded SDG-related activities and policies, and encourage the use of internet platforms, which deliver novel goods and services that relate to the seventeen SDGs. Less than half of UN members have FinTech laws and policies – making FinTech a ripe area for right-regulating. Unfortunately, in areas like institutional reform – no amount of money can guarantee achieving the SDGs, without wider legal and administrative reforms. And no clear data about the exact policies needed to help grow an economy (or pay for SDG spending) serve as any guide. With total investment in FinTech stuck at around $150 billion to $200 billion – the hoped for deluge of FinTech dollars on SDG activities may remain a trickle for years to come.

FinTech пропонує новий спосіб мобілізації ресурсів для всіх видів використання, в тому числі для фінансування сталого розвитку. Приблизно 3–13% фінансування, необхідного для досягнення цілей сталого розвитку ООН (ЦУР) – або приблизно від 50 до 125 мільярдів доларів США – можуть надходити від «Дивідендів FinTech». Такі дивіденди отримують від використання фінтех-платформ для збільшення заощаджень та інвестицій (загалом), спрямовування ресурсів на діяльність та політику, пов’язані з ЦУР, що фінансуються державою, а також приватно, а також заохочення використання інтернет-платформ, які пропонують нові товари та послуги, що стосуються сімнадцяти ЦУР. Менше половини членів ООН мають закони та політику щодо фінансових технологій, що робить фінтех дозрілою сферою для правильного регулювання. На жаль, у таких сферах, як інституційна реформа, жодна сума грошей не може гарантувати досягнення ЦУР без ширших правових та адміністративних реформ. І жодні чіткі дані про точну політику, необхідну для розвитку економіки (або оплати витрат на ЦУР), не можуть бути орієнтиром. Оскільки загальні інвестиції у фінтех застрягли на рівні приблизно від 150 до 200 мільярдів доларів – сподівання на те, що фінансові кошти фінансуються на діяльність ЦУР, можуть залишатися течією протягом багатьох років.
Michael B. The FinTech Dividend: How Much Money Is FinTech Likely to Mobilize for Sustainable Development? / B. Michael, T. Latkovska //Global Policy. - Vol .12. – Iss. 5. - Durham University, 2021. - Р. 677–688.
Keywords: FinTech Dividend; SDG funding; FinTech law; inclusive finance; #FinTech4SDGs; дивіденди з фінансових технологій; фінансування в рамках ЦУР; закон про фінансові технології; інклюзивне фінансування; Research Subject Categories::LAW/JURISPRUDENCE; Research Subject Categories::SOCIAL SCIENCES::Business and economics